Preliminary data on trade and management of rattan in and around Kisangani (Democratic Republic of Congo) - Kahindo, J.-M.; Lejoly, J.; Mate, J.-P.; Nasi, Robert (Stellenbosch University, 2011)
Rattan is an important non-wood forest product in the economy of Democratic Republic of Congo (DR Congo) and in the subsistence of populations in the Congo Basin. This paper presents preliminary results of a survey conducted with rattan stakeholders in Kisangani and the Yoko Forest Reserve (YFR) neighbourhood, in the Orientale Province, DR Congo. The aim of the study was to identify areas supplying rattan canes and to characterise the rattan sector in and around Kisangani. Over a 3-month period (104 days), canes traded from villages to Kisangani were recorded, and various rattan stockholders were interviewed with submitted questionnaires. According to preliminary results, 10 villages supply 71,709 linear metres of small-diameter cane monthly, of which 64,226 m are processed by 12 workshops i n LubungaCommune. Rattan items were found in 98% of 556 households studied in the six communes of Kisangani town. More trade data from different rattan stakeholders, together with ecological data are required to define appropriate management guidelines for sustainability of the resource.